Pelatihan Dramatic Reading untuk Peningkatan Kualitas Role Playing Siswa SMA Negeri 3 Takalar - Asis Nojeng; Faisal Faisal; Asri Ismail; Abdul Haliq; Edi Suhardi Rahman (Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to improve students’ role-playing quality through dramatic reading training at SMA Negeri 3 Takalar. The program was initiated in response to the school’s need to develop more active, expressive, and practice-based language and literature learning. The main problems faced by the partner school included students’ low self-confidence in performing in front of the class, limited ability to read texts expressively, insufficient understanding of characters in texts, and the need to strengthen teachers’ creative teaching strategies. The program was implemented through several stages, namely preparation, development of training materials, implementation of dramatic reading training, mentoring of role-playing practice, video documentation, evaluation, and reflection. The results showed that dramatic reading training improved students’ ability to read texts with better intonation, articulation, expression, and appreciation. Students also demonstrated increased confidence in performing, improved understanding of characters, and better collaboration in groups. For teachers, this program provided an alternative strategy for teaching language and literature in a more communicative, creative, and engaging way. In addition, the program produced several outputs, including training materials, dramatic reading practices, instructional video documentation, and a community service scientific article. Therefore, dramatic reading training can be considered an effective learning strategy to improve the quality of role playing, language skills, self-confidence, and students’ literary appreciation at school.